Implications of Alternative Measures of Natural Resource Scarcity - Brown, Gardner M.; Field, Barry C. (Journal of Political Economy, 1978)
We argue that the most commonly used measures of natural resource scarcity are deficient. The discussion begins with some general comments on natural resource scarcity, then turns to a description and evaluation of each of the major scarcity indices: unit cost, product output prices, and rental rates. Rental rates or a useful proxy, marginal discovery costs, are preferred over the rival measures. But there are important instances where good scarcity indicators may be entirely absent.